2017
DOI: 10.1136/bmjgh-2017-000345
|View full text |Cite
|
Sign up to set email alerts
|

Modelling historical changes in the force-of-infection of Chagas disease to inform control and elimination programmes: application in Colombia

Abstract: BackgroundWHO's 2020 milestones for Chagas disease include having all endemic Latin American countries certified with no intradomiciliary Trypanosoma cruzi transmission, and infected patients under care. Evaluating the variation in historical exposure to infection is crucial for assessing progress and for understanding the priorities to achieve these milestones.MethodsFocusing on Colombia, all the available age-structured serological surveys (undertaken between 1995 and 2014) were searched and compiled. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 33 publications
0
47
1
4
Order By: Relevance
“…There are a few possible reasons why this FOI analysis identified the oldest age group as having the highest risk of infection based on model AIC. Questions remain as to whether [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Furthermore, the oldest age group has a much larger age range than the others, and therefore represents a greater cumulative risk.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few possible reasons why this FOI analysis identified the oldest age group as having the highest risk of infection based on model AIC. Questions remain as to whether [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Furthermore, the oldest age group has a much larger age range than the others, and therefore represents a greater cumulative risk.…”
Section: Discussionmentioning
confidence: 99%
“…There are limitations to this study. The failure to interrupt intradomiciliary vectorial T. cruzi transmission in the Americas is likely to be linked not only to a lack of systematic implementation of vector control—particularly in hard-to-reach populations such as rural and indigenous communities [ 5 ]—but also to the existence of other T. cruzi transmission cycles, such as the presence of sylvatic vector populations in close contact with humans, against which IRS is not as efficacious as with domestic transmission [ 26 ]. Vector control has been very efficacious in areas with exclusively domiciliated vectors, as is the case of Central American countries [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of Chagas disease, the 2012 London Declaration and the World Health Organization (WHO) roadmap on Neglected Tropical Diseases proposed that by the year 2020, total interruption of intradomiciliary transmission in Latin America and provision of care to all infected patients should be achieved [ 4 ]. However, recent data suggest that antivectorial programs are not being sustained in all endemic countries or regions [ 5 ]. Furthermore, treatment coverage is as low as <1% of the infected population [ 6 ], and access to care remains limited in several countries [ 7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on two age-stratified serological studies, Salje et al used these approaches to show that, over the past 60 years, four distinct chikungunya outbreaks occurred in the Philippines, each affecting about a quarter of the population [49]. Similarly, combining age-stratified data from over 100 serosurveys, Cucunubá et al used catalytic models to quantify the impact of the Chagas' disease control and elimination programme in Colombia during the past three decades [50]. The study showed that, while the force of infection dropped by up to 90% in urban settings, it remained constant in remote areas, highlighting major geographic variations in the impact of the programme.…”
Section: Reconstructing Transmission History From Serological Datamentioning
confidence: 99%